PERANAN BANK INDONESIA DALAM MENGATASI PERGERAKAN INFLASI DENGAN INFLATION TARGETING FRAMEWORK - Erica, Denny (www.bsi.ac.id, 2015)
ABSTRACTThis study aims to find answers and explain the role of Bank Indonesia in overcoming inflation movements with the Inflation Targeting Framework (ITF) in Indonesia. In implementing monetary policy, Bank Indonesia has a framework called Inflation Targeting Framework (ITF), which adopts the exchange rate floating (free floating), with the framework of Bank Indonesia conduct the BI Rate as a policy instrument in reflecting the monetary policy stance , Regularly, Bank Indonesia to explain to the public about the assessment of the condition of inflation and the outlook for the future as well as the decisions taken. If the inflation target is not achieved the necessary explanations to the public and the steps to be taken to restore accordance with the inflation target.Characteristics of inflation in Indonesia is still likely to be influenced by inflation Volatile side with respect to disruption of production, distribution and primary commodity price shock. Moreover, shocks to inflation may also come from government policies related to prices of strategic commodities such as fuel oil (BBM) and other energy commodities (administered prices). To reach the target of low and stable inflation, it is necessary to control inflation through cooperation and coordination across agencies, between Bank Indonesia and the Government in order to support economic growth and improve people's welfare by maintaining the level of stability of the rupiah in Indonesia.